APPLICATION OF THINK PAIR SHARE (TPS) LEARNING MODEL TO IMPROVE STUDENTS' LEARNING INTEREST IN MATHEMATICS SUBJECTS IN GRADE V AT SDN 001/IX SENGETI - Rts. Mutmainnah; Ahmad Sayuti Nainggolan (PT. Jurnal Center Indonesia Publisher, 2025)
The background of the research is that students tend to be passive and afraid, and boring so that there is a lack of interest in learning students. The study aims to apply the Think Pair Share (TPS) model to improve students' interest in learning Mathematics in class V of Elementary School 001/IX Sengeti. The type of research is Classroom Action Research. The Action Model consists of 4 stages, namely planning, action, observation and reflection. The study was conducted in 2 cycles, cycle I as many as 2 meetings and cycle II was conducted in 2 meetings. Data collection in the form of teacher and student observation sheets and questionnaires. The results of the analysis of teacher observations in cycle I obtained a score of 72.05% and cycle II 90.43% in the very high category. While the results of the analysis of student observations in cycle I obtained a score of 72.5% and cycle II 90% in the very high category. Then the results of the analysis of student questionnaires obtained a score of 90% in the very high category. It can be concluded that the application of the Think Pair Share learning model can improve students' interest in learning